Missing the Target: Brazil's Agricultural Policy Indirectly Subsidizes Foreign Investments to the Detriment of Smallholder Farmers and Local Agribusiness - Corcioli, Graciella; Medina, Gabriel da Silva; Arrais, Cristiano Alencar (Frontiers in Sustainable Food Systems, 2022)
Currently there is controversy about the effect of direct foreign investment in the Brazilian agricultural sector, mainly due to the impact it has on small farmers, land use, the environment, and food security. In this context, Brazil finds itself in an even more delicate situation, since in order to remain a bulwark of the economy, Brazilian agribusiness depends heavily on public policies that directly impact its treasury. This suggests there is an indirect transfer of public resources to transnational companies involved in agribusiness production chains. This paper assesses the allocation of agricultural credits in Brazil and the market share held by Brazilian groups, vis-à-vis multinational corporations in the agribusiness supply chains. The study was carried out analyzing the three largest supply chains established in the country: soybean, corn, and cattle. Results reveal that 75% of the operating credit (crédito de custeio), which represents 60% of the total government credit in Brazil, goes directly to soybean, corn, and cattle farmers. Most of this subsidized credit budget goes to the soybean farmers, which are mostly encompassed by large farmers. Results also reveal that 76.1% of the soybean supply chain in Brazil is controlled by foreign multinational corporations. These findings suggest that resources invested in large farmers that take part in supply chains controlled by multinational foreign groups end up indirectly financing foreign companies to the detriment of local smallholder farmers and domestic agribusiness. This highlights the need for restructuring Brazilian agricultural policy in favor of family farmers and domestic agribusiness.